The Role of AI Trust Factors in Enhancing Talent Acquisition Processes: A Study on HR Professionals Across Various Sectors - Rasmi Lata Nayak (Journal of Informatics Education and Research, 2024)
The introduction of artificial intelligence (AI) into human resource management has given a new face to talent acquisition, which will lead to more streamlined and smarter methods to search for available candidates. However, the growth of AI in recruitment depends to a large extent on how much confidence HR professionals invest in these technologies. In an increasingly AI-powered world, how can we help HR professionals to be confident enough with these systems that they actually improve their talent acquisition processes rather than hinder them? This is the context of the present study seeking to provide insight into this trust. The purpose of this study is to investigate the effect of trust factors in AI—in terms of reliability, credibility, technical competency, and relative advantage—on HR professionals' trust in AI and how a secondary process will impact talent acquisition performance across different industries. It was a quantitative survey involving 331 HR professionals from various sectors like IT, power distribution, FMCG, and healthcare. Structural equation modelling (SEM) was applied to examine the direct and indirect effects of perceived AI trustworthiness factors in predicting trust toward AI and talent acquisition outcomes. Items measuring the AI trust factors demonstrated good internal consistency overall. Still, none of the AI trust factors had a statistically significant direct effect on either trust in AI or the effectiveness of talent acquisition processes. Interesting as it may sound, this means that some of the traditional trust related factors might not be enough by themselves to accelerate AI adoption in HR. This work points to a requirement for a more holistic strategy towards developing trust in AI within the HR context, taking into account other factors like organizational culture and personal technology experiences. This four-part series on the dynamics of AI and recruitment is pivotal if AI is to be a more effective and efficient element of global talent acquisition. Findings from this research highlight the need to focus on the complexity of adoption in AI to truly realize its transformative potential in transforming HR practices.